2019
DOI: 10.1108/nfs-05-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Does combination of Lactobacillus rhamnosus Heriz I and beta glucan improve quality of life in women with breast cancer receiving chemotherapy?

Abstract: Purpose This paper aims to study the impact of combination Lactobacillus Rhamnosus Heriz I and Beta glucan on quality of life (QOL) in breast cancer (BC) patients receiving chemotherapy. Design/methodology/approach In all, 30 women with BC were enrolled in this randomized double-blind placebo-controlled clinical trial. Intervention group received either daily one capsule of L. rhamnosus strain Heriz I (2 × 107 CFU) and two 10-mg capsules of soluble1–3,1–6,D-beta glucan and the placebo group receiving placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…The consumption of functional foods did not affect HrQoL during the COVID-19 pandemic. The finding was dissimilar with the results obtained by Zhang et al (2016) and Monshikarimi et al (2020).…”
Section: Health-related Quality Of Lifecontrasting
confidence: 98%
See 1 more Smart Citation
“…The consumption of functional foods did not affect HrQoL during the COVID-19 pandemic. The finding was dissimilar with the results obtained by Zhang et al (2016) and Monshikarimi et al (2020).…”
Section: Health-related Quality Of Lifecontrasting
confidence: 98%
“…The research of Zhang et al (2016) revealed that the consumption of functional foods improved HrQoL. This finding was supported by Monshikarimi et al (2020). Therefore, this study postulated that the affordability of and customer loyalty toward functional foods would positively affect HrQoL during the COVID-19 pandemic.…”
Section: Health-related Quality Of Lifesupporting
confidence: 51%
“…The higher dose of synbiotic supplement or longer follow-up duration may affect this difference of estimation and can be evaluated in future researches. Due to ethical issues and limited studies in this field [ 32 , 33 ], we could not include a separate group that had just received synbiotic supplementation, which could clarify the independent effect of synbiotic on quality of life. According to the results of this study and lack of side effects, it seems that the effect of synbiotics alone can be assessed in the next study.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life represents a wide, multi-dimensional concept including good physical, mental and social health as well as satisfaction with life circumstances (Monshikarimi et al, 2019). According to the studies, diabetic patients have a poor quality of life (Sothornwit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%